Going Somewhere Else: A Qualitative Exploration of the Experience of Foreign-Born Leadership Educators - Bourgeois, Jeff; Zare , Sara (Journal of Leadership, Accountability and Ethics, 2021)
Leadership is a discipline influenced by culture. It stands to reason that cultural identities of students and educators of leadership steer their leadership identities. This project investigates the implications of culture on Leadership Educator identity in foreign-born teachers—persons whose national cultural identity is different than the one in which they teach. Using semi-structured interviews of participants from around the world, this qualitative study identifies shared experiences, challenges, and discoveries of foreign-born Leadership Educators. Findings will provide insight for institutions supporting foreign-born leadership faculty, and also inform the development of Leadership Educator identities in individuals planning to teach leadership abroad.